2019
DOI: 10.1097/jxx.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention to enhance nurse practitioner role transition in the first year of practice

Abstract: Background and Purpose: Role transition is a natural process that occurs when the registered nurse pursues additional education to become a nurse practitioner (NP). Role transition generates feelings of anxiety and insecurity, leading to a longer and more tumultuous adjustment. This study investigated whether an evidence-based role transition webinar would support NP role transition during this critical period. Methods: This study was a nonrandomized, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…Those who completed the VA fellowship program reported that the professional development activities the program offered contributed to a smoother professional transition . The online intervention focused on providing new graduates with evidence about the challenges of the transition period, thus socializing them to the demands of their new roles; however, results did not support this intervention as linked to improved role transition …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Those who completed the VA fellowship program reported that the professional development activities the program offered contributed to a smoother professional transition . The online intervention focused on providing new graduates with evidence about the challenges of the transition period, thus socializing them to the demands of their new roles; however, results did not support this intervention as linked to improved role transition …”
Section: Resultsmentioning
confidence: 98%
“…Table details the characteristics of the included studies. Four articles representing three studies examined fellowship program interventions and one considered a webinar intervention . Sample sizes ranged from 7 to 36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations